Coal Mine Gas Wireless Monitoring System Based on WSNs - Qin Xianli; Fu Mingchao; Shen Bin (2011 Second International Conference on Digital Manufacturing and Automation, 2011)
In order to make up the shortage of mine cable monitoring system, and build the coal mine internet of things more quickly. The gas wireless monitoring system was designed by using cc2430 which was used to build Wireless Sensor Networks (WSNs), and combining MCU technology, sensor technology, store display and CAN bus communication technology. The overall framework of the system was given, and the WSNs was designed detailed, including wireless gas sensor, monitoring sub-station and monitoring gateway's hardware and software design. The system effectively solves the shortcomings of present monitoring systems, and can be used, as a new generation of monitoring system, to promote, due to its strong expansion and easy operation.